Food and feeding strategy of sunrise goatfish Upeneus sulphureus, Cuvier (1829] in Kendari Bay, Southeast Sulawesi - Asriyana Asriyana; Nur Irawati (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2018)
Knowledge of food and feeding strategies are essential to understand the ecological role and productive capacity of fish populations. This information is critical for development of conservation and management plans of fishery resources. This study aimed to analyze the food and feeding strategy of sunrise goatfish in Kendari bay. Sampling was done monthly from May to November 2016, with bottom experimental gillnets with mesh size ¾, 1, 1 ¼, and 1 ½ inches. The food habits was analyzed using index of preponderance; while feeding strategy was determined by Amundsen modified Costello method. There were 386 fish with total length and weight ranged from 46.0-176.0 mm and 3.0-67.1 g, res-pectively. The fish were categorized into 3 groups based on the length sizes. The length sizes were classified into small size (45.0-69.7 mm), medium size (69.8-94.3 mm) and large size (94.4-119.0 mm). Twenty eight species of organisms were found in the digestive system of the sunrise goatfish dominated by the phytoplankton genus Thallasiothrix. The sunrise goatfish has significant dietary changes with increasing total length and time. The sunrise goatfish developed mix feeding strategies; specialist and generalist. Generalist strategy developed for all prey, except Thallasiothrix obtained by spesialist strategy. Abstrak Pengetahuan tentang makanan dan strategi pola makan adalah penting untuk memahami peran ekologi dan kapasitas produktif populasi ikan. Informasi tersebut sangat penting untuk pengembangan rencana konservasi dan pengelolaan sumber daya ikan. Penelitian ini bertujuan untuk menganalisis makanan dan strategi pola makan ikan kuniran di per-airan Teluk Kendari. Pengambilan contoh dilakukan sekali sebulan dari bulan bulan Mei sampai November 2016, de-ngan jaring insang eksperimental berukuran mata jaring ¾, 1, 1 ¼, dan 1 ½ inci. Kebiasaan makanan dianalisis meng-gunakan metode indeks bagian terbesar, sedangkan strategi pola makan ditentukan melalui metode Costello yang dim-odifikasi oleh Amundsen. Jumlah ikan yang terkumpul sebanyak 386 ekor dengan kisaran panjang total 46,0–176,0 mm dan kisaran bobot 3,0–67,1 g. Ikan dikelompokkan kedalam tiga kelompok ukuran yaitu ukuran kecil (46,0–90,0 mm), sedang (91,0–134,0 mm), dan ukuran besar (135,0–176,0 mm). Ditemukan 28 jenis organisme makanan dalam saluran pencernaan ikan kuniran. Menu makanan didominasi oleh kelompok fitoplankton genus Thallasiothrix. Ikan kuniran mengalami perubahan makanan yang signifikan sejalan dengan bertambahnya ukuran panjang tubuh dan waktu. Dalam memanfaatkan makanan di perairan, kuniran umumnya mengembangkan strategi pola makan campuran antara generalis dan spesialis. Strategi pola makan generalis dikembangkan untuk memperoleh semua jenis mangsa, kecuali mangsa Thallasiothrix diperoleh dengan strategi pola makan spesialis.